Stimulating Higher Education Students' Entrepreneurial Intention: Observing the Influence of Entrepreneurship Education and Lecturers' Personal Competence - Sariat Arifia; Katon Pratondo; Zaid Zaid; Ace Somantri; Mahbub Pasca Al Bahy (Universitas Sebelas Maret, 2024)
Entrepreneurship is becoming an increasing topic of discussion. It has attracted the attention of academics worldwide due to its beneficial impact on economic and social development worldwide. For this reason, it is essential to stimulate the intention to engage in entrepreneurial endeavors as early as possible, preferably while still a student. Unfortunately, no research has explored the role of higher education, such as universities, as providers and supporters of a supportive environment in fostering entrepreneurial intentions, which can ultimately produce entrepreneurs. Based on these problems, this research examines essential factors such as entrepreneurship education and lecturers' competencies, which influence students' entrepreneurial intentions. Using a quantitative method involving 314 respondents through Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, this research concludes that entrepreneurship education and lecturers' personal competencies positively and significantly influence students' entrepreneurial intention. This research also offers educational institutions and the government an increase in students' intentions to become entrepreneurs. On the other hand, this study suggests that both the mixed methods approach and longitudinal models should be expanded to provide a more thorough knowledge of the readiness of individuals to engage in entrepreneurial enterprise.